Balloon Temponade to Prevent Primary PPH in Jaundice - A Prospective Study - Siddiqui, Maruf; Rashid, Maliha (Journal of Bangladesh College of Physicians and Surgeons, 2010)
This prospective interventional study was carried out on 40 intrapartum jaundice patients admitted in the Department of Obstetrics and Gynaecology, Dhaka Medical College Hospital during January to December 2004. The purpose of the study was to evaluate the effectiveness of prophylactic intrauterine hydrostatic balloon/condom temponade in addition to other conventional methods to prevent and control postpartum haemorrhage in patients with jaundice, to detect the prevalence of different etiological agents responsible for jaundice and to assess the foeto-maternal outcome in this study group. Prophylactic intrauterine hydrostatic balloon temponade was inserted in all of the 40 cases which showed an excellent effectiveness in preventing postpartum haemorrhage in patients with jaundice. The study also showed increased prevalence of Hepatitis E virus (HEV) and a high proportion of perinatal deaths in the study population. DOI: 10.3329/jbcps.v26i1.4229 J Bangladesh Coll Phys Surg 2008; 26: 22-25